Chronic intermittent hypoxia impairs BM-MSC osteogenesis and long bone growth through regulating histone lactylation - Fang Chen; Meizhen Gu; Hongming Xu; Shasha Zhou; Zilu Shen; Xiaoyan Li; Liangchao Dong; Pin Li (Journal of Translational Medicine)
Abstract Background Chronic intermittent hypoxia (CIH) caused by OSA often results in serious complications. However, the adverse effects of CIH on bone growth and development are often overlooked. Methods CIH intervention was conducted using an OxyCycler model A84 system for 8 h per day (from 8:00 a.m. to 4:00 p.m.) over a period of 4 weeks. Body and femur lengths were measured, and micro-CT, histological analysis, and ELISA were performed to evaluate femoral development. Metabolomic, single-cell transcriptomic, Western blot, and ChIP‒qPCR analyses were conducted to explore the potential mechanisms underlying CIH-induced inhibition of long bone growth. T0070907 was administered intraperitoneally (0.5 mg/kg) every two days to investigate its effect on long bone growth under CIH conditions. Results Here, we showed that CIH stimulation during long bone development significantly inhibited long bone growth. Multiomics analysis revealed that CIH induces anaerobic glycolysis in bone marrow mesenchymal stem cells (BM-MSCs), promotes adipogenic differentiation, and reduces their osteogenic differentiation capacity. Mechanistic studies demonstrated that CIH-induced lactate accumulation enhances lactylation at histone H3 lysine 18 (H3K18) on the PPARγ promoter in BM-MSCs, leading to the transcriptional activation of PPARγ and a consequent imbalance between the adipogenic and osteogenic differentiation of BM-MSCs. The PPARγ inhibitor T0070907 could partially rescue long bone developmental disorders induced by CIH. Conclusions Our findings reveal an epigenetic mechanism underlying CIH-induced long bone dysplasia and highlight T0070907 as a promising targeted therapeutic agent.